PP.31.10: FACTORS INVOLVED IN WHITE COAT HYPERTENSION IN PATIENTS WITH CHRONIC KIDNEY DISEASE. (June 2015) - Psounis, K.; Kolyvas, G.; Oikonomaki, T.; Geladari, H.; Evangelatou, E.; Kritsos, K.; Nikolopoulou, N.; Apostolou, T.; Andreadis, E.
Abstract : Objective: To evaluate the value of different cardiovascular risk factors on white coat hypertension (WCH) prevalence in hypertensive patients with chronic kidney disease (CKD). Design and method: Individuals with CKD stage III to V were evaluated with 24-hour ABP monitoring (Microlife WatchBP O3). Subjects were characterized as controlled when mean 24-hour blood pressure (BP) was < 130/80mmHg, mean awake BP < 135/85mmHg and mean asleep BP < 120/70mmHg. WCH was defined for those with BP readings at least 140/90mmHg in the office and a mean 24-hour ABP SBP/DBP < 130/80mmHg, awake < 135/85mmHg or nocturnal < 120/70mmHg. Body mass index (BMI) was derived by dividing weight (Kg) by the square of height (m2). Renal impairment and staging was assessed by estimated glomerular filtration rate (eGFR). Results: Independent sample t-test analysis and Chi-square test were used in order to detect statistical correlations. A total of 89 subjects with complete ABP monitoring were analyzed (mean age 65.3 ± 12.4 years, men 66%, diabetics 35%, current smokers 12%, history of cardiovascular disease 21% and eGFR 32.4 ± 13.7 ml/min/1.73 m2; the mean number of antihypertensive drugs received was 2.4 ± 1.2). The prevalence of WCH was 26.9 %. There was strong correlation between diabetes, body mass index (BMI) and WCH (p = 0.014 and 0.016, respectively), whereas age, sex, history of cardiovascular disease, eGFR and smoking had no impact on WCH (p = 0.22, 0.5, 0.3, 0.9 and 0.34, respectively). Conclusions: The overall prevalence of WCH appears to be frequent in individuals with CKD. Factors related to the increased prevalence are diabetes and body mass index. Those patients would be followed-up closely in order to evaluate their progress to sustained hypertension.